2018
DOI: 10.1111/odi.12896
|View full text |Cite
|
Sign up to set email alerts
|

Oral yeast colonization in patients with primary and secondary Sjögren's syndrome

Abstract: This study showed that C. albicans is the most prevalent yeast, but also that a variety of other yeast species can colonize the oral cavity of Sjogren's syndrome patients. The identification of most of the colonies was not obtained by culturing-PCR methods combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…Effects of decreased salivary secretion on the oral microbiome have been discussed in the context of Sjögren's syndrome and side effects of radiotherapy and drug therapies [33][34][35]. Such studies have commonly reported higher detection rates of Lactobacilli and C. albicans; however, the present study showed a low detection rate of Lactobacilli and no signi cant difference between children with DS and ND group.…”
Section: Discussioncontrasting
confidence: 59%
“…Effects of decreased salivary secretion on the oral microbiome have been discussed in the context of Sjögren's syndrome and side effects of radiotherapy and drug therapies [33][34][35]. Such studies have commonly reported higher detection rates of Lactobacilli and C. albicans; however, the present study showed a low detection rate of Lactobacilli and no signi cant difference between children with DS and ND group.…”
Section: Discussioncontrasting
confidence: 59%
“…In fact, some authors have studied both types of saliva in pSS patients and have reported high Candida counts associated to both lower rates of SWS and UWS, although without demonstrating statistical significance ( 22 , 23 ). Similarly, there are studies reporting that when C. albicans is higher UWS is decreased ( 2 , 24 , 25 ), some demonstrating a significant relationship ( 2 , 25 ). In other studies, however, the association was with SWS rather than UWS ( 26 ).…”
Section: Discussionmentioning
confidence: 92%
“…Primary Sjögren’s syndrome (pSS) is a systemic autoimmune exocrinopathy that damages the salivary and lacrimal glands, resulting in dry eyes and hyposalivation ( 1 , 2 ). Saliva contains IgA, lysozyme and lactoferrin, which are important antimicrobial defence mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Sjögren syndrome (SS) is a systemic autoimmune exocrinopathy of unknown aetiology. Different predisposing factors along with several immune-related processes have been described in its pathogenesis, supporting the idea of a multifactorial disease (1). It can occur as primary SS (pSS), when it courses as an isolated disorder or as secondary SS when it appears in association with another systemic autoimmune disease (2).…”
Section: Introductionmentioning
confidence: 85%
“…It can occur as primary SS (pSS), when it courses as an isolated disorder or as secondary SS when it appears in association with another systemic autoimmune disease (2). pSS usually emerges in the 4 th -5 th decade of life, affecting women more than men, in a proportion 9:1, and its prevalence rates range between 0.1 to 4.8% (1,3,4). pSS is a chronic inflammatory disease characterized by lymphocytic infiltration of the lacrimal and salivary glands resulting in the primary symptoms of this condition: presence of dry eyes and hyposalivation.…”
Section: Introductionmentioning
confidence: 99%